Serological and molecular analysis of parvovirus B19 infection in Mayan women with systemic lupus erythematosus in Mexico. (Colombia Medica, 2017)
Background:Systemic lupus erythematosus (SLE) is a systemic autoimmune disease that mainly affects women, characterized by the production of autoantibodies. Its causal agent is unknown, but the combination of environmental, hormonal and genetic factors may favor the development of the disease. Parvovirus B19 has been associated with the development of SLE, since it induces the production of anti-single stranded DNA antibodies. It is unknown whether PV-B19 infection is an environmental factor that trigger or reactivate SLE in the Mexican Mayan population.Aim:A preliminary serological and molecular study of PV-B19 infection in Mayan women with established SLE was done.Methods:IgG and IgM anti PV-B19 were evaluated in 66 SLE patients and 66 control subjects, all women of Mayan origin. Viral DNA and viral load were analyzed by qPCR.Results:Insignificant levels of IgM were observed in 14.3% (4/28) of the patients and 11.4% (4/35) of control subjects. IgG was detected in 82.1% (23/28) of the patients and 82.9% (29/35) of control subjects, but were significantly higher in patients. Viral DNA was found in 86.0% (57/66) of the patients and 81.0% (54/66) of control subjects. Viral load, quantified in 28/66 patients and 31/66 controls which were positive for IgM and IgG, was significantly higher in controls.Conclusion:The high prevalence of PV-B19 in Yucatan, and the presence of IgM, IgG, and viral load in Mayan women with established SLE suggest that PV-B19 infection could be an environmental factor to trigger or reactivate SLE.